PENGARUH KOMISARIS INDEPENDEN, RETURN ON ASSET, DEBT DAN CURRENT RATIO TERHADAP FINANCIAL DISTRESS PADA PERUSAHAAN MANUFAKTUR SUB SEKTOR MAKANAN DAN MINUMAN PERIODE 2020-2022 - Nazar Faddilah; Hafiz Ali; Raihan Alvero (Jurnal Riset Multidisiplin Edukasi, 2025)
This study aims to analyze the effect of Independent Commissioners, Return on Assets (ROA), Debt Ratio, and Current Ratio on Financial Distress in manufacturing companies within the food and beverage sub-sector listed on the Indonesia Stock Exchange (IDX) during the 2020–2022 period. Financial Distress is measured using the Zmijewski model. This research employs a quantitative approach with multiple linear regression analysis processed using SPSS version 25. The research sample consists of 30 observational data obtained from 10 companies over a three-year period. The results indicate that Return on Assets and Debt Ratio have a significant effect on Financial Distress. Meanwhile, Independent Commissioners and Current Ratio do not have a significant effect on Financial Distress. Simultaneously, all independent variables significantly affect Financial Distress. The Adjusted R Square value of 0.972 indicates that the independent variables are able to explain 97.2% of the variation in Financial Distress.